2015
DOI: 10.1177/8755122515579461
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D Levels During Pregnancy and Postpartum Depression

Abstract: Article BackgroundSeveral studies have found that low levels of serum 25-hydroxyvitamin D (25(OH)D) are linked to many diseases and disorders such as premenstrual syndrome, nonspecific mood disorder, major depressive disorder, cancer, autoimmune disorders, bone diseases, cardiovascular diseases, preeclampsia, seasonal affective disorder, and post-partum depression (PPD). 1-4 It is suggested that vitamin D is a potential neurosteroid and that it is found in high concentrations in the amygdala, thalamus, hypotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Ultimately, 21 eligible studies were assessed, and 14 of these were selected for full review, all of which were full-text publications [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Articles were excluded for the following reasons: a general review [ 36 ], study of other nutritional factors, e.g., milk and calcium [ 37 , 38 ], lack of comparison group [ 39 ], not measuring the outcome of interest/not population of interest [ 40 , 41 ], or published as an abstract [ 42 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 21 eligible studies were assessed, and 14 of these were selected for full review, all of which were full-text publications [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Articles were excluded for the following reasons: a general review [ 36 ], study of other nutritional factors, e.g., milk and calcium [ 37 , 38 ], lack of comparison group [ 39 ], not measuring the outcome of interest/not population of interest [ 40 , 41 ], or published as an abstract [ 42 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, not all of the studies reported data on these factors or the percentages of women with deficient or insufficient levels. A recent review investigated vitamin D levels measured during pregnancy and their association with postpartum depression, the results of which suggested a correlation (Mahmood et al, 2015). Three studies were included, one of which classified depression by antidepressant use (Nielsen et al, 2013).…”
Section: Several Factors Can Influence Vitamin D Levels Such As the Season Of Vitamin D Measurementsmentioning
confidence: 99%
“…VD is a steroid hormone that is produced by our bodies after being exposed to ultraviolet B radiation through the skin,[ 26 ] it can also be acquired from food like fish, egg yolk, liver oil, beef liver, portabella mushrooms, fortified foods such as breakfast cereal and milk. [ 27 28 29 ] Ultraviolet light converts 7-dehydrocholesterol to pre- VD, which is convert to cholecalciferol (VD3),[ 24 ] that exhibits no biological activity within the body. Then it passes through two hydroxylation steps to be activated, the first one in the liver to produce 25hydroxy vitamin D (25(OH)D), which is the predominant vitamin form in our blood,[ 30 ] and the second hydroxylation occur mainly inside the kidney, brain, and immune system by 1alpha-hydroxylase using specialized cells to produce the functional form of VD, which is called calcitriol.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 42 ] Increased circulating 25(OH)D concentrations following 8-week VD supplementation (50,000 IU) resulted in a significant decrease in Beck Depression Inventory-II (BDI-II) scores in patients with mild-to-moderate depression. [ 42 ] The relationship between VD levels and PPD is controversial; few studies revealed the association between VD level and PPD,[ 7 13 29 43 ] while others showed no association. [ 7 ] This study aims to review the studies concerning the association between 25(OH)D levels during pregnancy and PPD development.…”
Section: Introductionmentioning
confidence: 99%